Preparação e caracterização de scaffolds a base de polímeros naturais para aplicações biomédicas - Lovato, Bárbara Ferreira (2018)
The present study aims at preparing three-dimensional porous structures, chitosan based scaffolds, that allow the regeneration of the bone tissue simultaneously with the degradation of this material. The scaffolds were produced with nanocellulose and nanocellulose/tannin emulsions, acting as reinforcing fillers. A method based on freezing and lyophilization was used to obtain the scaffold. To optimize the process, several concentrations of chitosan (1.5, 2, 3, 4, 5, 6 and 8%) were tested and two dissolution times: 24h and 48h. The influence of freezing methods, such as liquid nitrogen (N2(liq)), ultrafreezer and freezer on the structure and morphology of the materials were analyzed. Neutralization treatments (ethanol and sodium hydroxide) were also studied. The characterization of the natural chitosan was carried out through analyzes such as degree of deacetylation (DD), crystallinity index (CI), molar mass (MM) and thermal properties. The scaffolds were characterized by Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), Thermal Analysis (DSC and TGA) and mechanical tests. The materials that presented a more regular structure, considering its porosity, pore size, interconnectivity and other characteristics were those with 4 and 6%(m/v) of chitosan concentration. The dissolution time of chitosan in acetic acid did not show influence on the structure, so it a 24h time period was elected because it is the shortest time for the dissolution of this material. The freezer proved to be the most efficient freezing process, indicating that the technique used generates changes in morphology and porosity. The tested neutralization method that better played its role was ethanol, as it maintained the structure more effectively. Due to the its solubility in water, crosslinking the obtained scaffold with glutaraldehyde agent was required.